2013
DOI: 10.1186/1748-5908-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Public health program capacity for sustainability: a new framework

Abstract: BackgroundPublic health programs can only deliver benefits if they are able to sustain activities over time. There is a broad literature on program sustainability in public health, but it is fragmented and there is a lack of consensus on core constructs. The purpose of this paper is to present a new conceptual framework for program sustainability in public health.MethodsThis developmental study uses a comprehensive literature review, input from an expert panel, and the results of concept-mapping to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
456
0
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(544 citation statements)
references
References 33 publications
11
456
0
23
Order By: Relevance
“…In this sense, all the means dedicated to establish quaternary prevention are powerful tools to avoid the chaos and the terrible waste of resources either of human or economic, leading to a more sustainable health care by effectively implementing and maintaining of evidence-based policies and activities. 22 The rules in terminological development aspire to cover the whole field of a concept and, in the meantime, they help to avoid the noise due to proxy and not exactly related issues. This refers to exhaustivity and specificity in information retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, all the means dedicated to establish quaternary prevention are powerful tools to avoid the chaos and the terrible waste of resources either of human or economic, leading to a more sustainable health care by effectively implementing and maintaining of evidence-based policies and activities. 22 The rules in terminological development aspire to cover the whole field of a concept and, in the meantime, they help to avoid the noise due to proxy and not exactly related issues. This refers to exhaustivity and specificity in information retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest and investment in disseminating and translating effective study interventions more broadly to target populations [17][18][19]. Political support, funding agency priorities, capacity of the dissemination organization, and knowledge of researchers in how to apply research findings can influence the success of study translation [20][21][22][23]. Although many researchers have dissemination expectations from funders [20], the majority of public health professionals spend little time and efforts on program dissemination [24], and few studies reported sustainability and challenges of disseminating an online decision aid tool from an effective intervention study.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, public health programs have only proven to be beneficial to communities over time if the community is able to sustain the initiatives. [5] There are numerous barriers associated with sustaining relationships and commitments to community programs, such as lack of resources and challenges in maintaining morale. [6] Academic partners play a key role in catalyzing change in a community, but it is the engage-ment of community members that yields a sustainable change overtime.…”
Section: Introductionmentioning
confidence: 99%